(untitled) (Texas Journal of Medical Science, 2024)
The relevance of this issue is due to the intensive development and introduction of the latest technologies in modern surgical interventions, including joint replacement, and a significant expansion of indications for surgical treatment. We have already pointed out that in the vast majority of patients of these operations, elderly and senile people with various comorbidities and, in some cases, severely disabled, burdened with severe pain for many months and years, which leads to whole complexes of somatic reactions. and deviations in the clinical status of patients. All this greatly complicates the choice of the method of anesthesia and postoperative analgesia. After all, postoperative pain is the result of surgery, but its treatment is not just a humane requirement, but a key aspect of postoperative therapy. Endoprosthetics of the joints of the lower limb is also a very traumatic intervention and, in some cases, is accompanied by significant blood loss. In the postoperative period, venous thrombosis and PE are the most dangerous [152; pp.101-106, 151; pp. 1018-1025, 72; pp.455-461]. In connection with the above, anesthesia should correspond to the nature of this intervention: completely block nociceptive impulses, maximally reduce perioperative blood loss and the need for donor blood components, the likelihood of developing thrombotic complications in the postoperative period, and the severity of postoperative pain syndrome [18; pp.210-212]. All these requirements are met to the maximum extent by the methods of central segmental blockades [92; pp. 810-814, 188; pp.193-199].